Predictive risk factors of acute kidney injury after cytoreductive surgery and cisplatin-based hyperthermic intra-peritoneal chemotherapy for ovarian peritoneal carcinomatosis. Issue 2 (February 2019) - Angeles, Martina Aida; Quenet, François; Vieille, Pierre; Gladieff, Laurence; Ruiz, Jean; Picard, Muriel; Migliorelli, Federico; Chaltiel, Leonor; Martínez-Gómez, Carlos; Martinez, Alejandra; Ferron, Gwénaël
Abstract : Objective: The aim of our study was to assess the incidence and identify the predictive risk factors of acute kidney injury after cytoreductive surgery and cisplatin-based hyperthermic intra-peritoneal chemotherapy. Methods: This is a retrospective study from two centers evaluating patients with advanced or recurrent ovarian cancer who underwent cytoreductive surgery followed by cisplatin-based hyperthermic intra-peritoneal chemotherapy from January 2007 to December 2013. Patients were classified into two groups according to the occurrence of acute kidney injury, defined as a glomerular filtration rate at post-operative day 7 25% lower than at day 0. We also evaluated acute kidney injury following Risk, Injury, Failure, Lost and End-stage kidney function criteria. Univariate and multivariate analyses were conducted in order to assess the association between different variables and the occurrence of acute kidney injury. Results: Sixty-six patients were included: 29 (44%) underwent first-line treatment and 37 (56%) were treated for recurrent disease. The incidence of post-operative acute kidney injury was 48%. After multivariate analysis, hypertension (OR 18.6; 95% CI 1.9 to 182.3; p=0.012) and low intra-operative diuresis (OR 0.5; 95% CI 0.4 to 0.8; p=0.001) were associated with acute kidney injury. Conclusion: The incidence of acute kidney injury after cytoreductive surgery and cisplatin-based hyperthermic intra-peritoneal chemotherapy was high. Hypertension and low intra-operative diuresis were independent risk factors for this complication. Adequate peri-operative hydration, in order to maintain correct diuresis, could decrease the occurrence of acute kidney injury in patients undergoing cytoreductive surgery plus hyperthermic intra-peritoneal chemotherapy.